Medicinal Mushrooms Cordyceps as a New Source of Bioactive Compounds and Their Complexation With Silver Ions - Uhrinová Anna; Maľučká Lucia Ungvarská (Sciendo, 2024)
Mushrooms from the genus Cordyceps are characterized by a wide range of biological effects due to the diverse amount of substances contained in them and are an important source of bioactive compounds. In China, mushrooms of the genus Cordyceps have been used as a medicinal preparation of traditional Chinese medicine for centuries. So far, a considerable number of studies have been conducted that focused on analyzing the effects of Cordyceps, which include their antioxidant, antibacterial, immunomodulatory, antidiabetic, antitumor, and many other effects. The ability of fungi to form complexes with various metals is also interesting. It is believed that polysaccharides are the main component of the extracts involved in the complexation with metals, after which their biological effects are improved and deepened. The work deals with the comparison of the antioxidant and antibacterial effects of Cordyceps extracts with extracts of this mushroom enriched with silver ions. Based on scientific studies, it is assumed that there is a complexation between the chemical compounds of the extracts and silver.